KONSTRUKSI MEDIA MASSA DALAM PROSES PILKADA GUBERNUR DKI JAKARTA - Nugroho, Ari Cahyo (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2013)
As a nation who adheres to the principle of unity in diversity (bhinneka), the issue of SARA (tribe, religion, race, and inter- groups) become a thing that is extremely sensitive. In the second round election for regional chief DKI governence, SARA issues raised by various mass media. The issue further sharping, with Rhoma Irama statement, who considered attack jakowi-ahok. Tempo Newspaper as one of independent media, used as a source of in this research. This research is a descriptive analysis, using framing method. The preaching of Tempo Newspaper associated with this research is collected and analysed using a frame entman. The results show that Koran Tempo display issues only focus on one object i.e. Rhoma Irama, related SARA in the election of Head Region DKI Jakarta (the Governor and the Deputy Governor). With the theme minored as a legal case. Koran Tempo seemed more focused on the case of Rhoma Irama as SARA case from the legal issues, who outbox another candidate. Koran Tempo had 8 news coverage relating to SARA, and the dominance is Rhoma Irama. In this case, Rhoma Irama declare that Muslims Jakarta, mustnât choose the leaders of non-Muslims, according to the media, indirectly attacking pair candidates Joko Widodo-Basuki Tjahaja. Of overall conclusions, Koran Tempo seen load balance in news coverage of the case of SARA